Development economics through the decades : a critical look at 30 years of the world development report - Yusuf, Shahid; Deaton, Angus (Washington, D.C. : World Bank, 2009)
This book is a masterful overview of what has at the same time been 30 years of develoment economies at the World Bank.
Includes bibliographical references (p. 157-182) and index.
aug 06/06/13
Loans
Keywords: Development economics